Characterization of a PCV2d-2 isolate by experimental infection of pigs - Vilmos Palya; Zalán G. Homonnay; Tamás Mató; István Kiss (Virology Journal, 2018)
Abstract Porcine circovirus type 2 (PCV2), a highly prevalent, economically important swine pathogen is classified into different genotypes (PCV2a-f) based on phylogenetic analysis. Since the introduction of extensive vaccination programs, at least two major shifts have been observed in the prevalence of PCV2 genotypes. The first genotype shift from 2a towards 2b occurred around 2003, while in recent years, we are witnessing the second change in genotype prevalence from the predominant 2b towards 2d. In this study, a PCV2d-2 isolate was characterized as a potential challenge virus for the evaluation of PCV2 vaccine efficacy. Ten-week-old pigs carrying low to moderate levels of maternally derived antibodies to PCV2 were infected with the isolate by the nasal route. Over the next 4 weeks post-infection, the pigs were monitored for the presence of viremia, fecal virus excretion, and humoral immune responses. At the end of the post-infection observation period, samples were taken from the mediastinal and mesenteric lymph nodes of the animals and tested for viral load. The gradual depletion of maternally derived antibodies in the sera of piglets was demonstrated by ELISA and virus neutralization tests. Following experimental infection by PCV2d-2, specific IgM antibodies were first detected at 14 days post challenge (dpch), while IgG class antibodies were first detected at 21 dpch. Both viremia and virus shedding could be detected at 7 dpch, in 36 and 50% of the pigs, respectively. The proportion of shedders reached 100% by 14 dpch and remained at this level, while viremia was demonstrated in 86, 100, and 100% of the pigs at 14, 21, and 28 dpch, respectively. Both the mediastinal and mesenteric lymph nodes contained high levels of virus (7.6 and 8.5 log10 copies/mg tissue, respectively).